Study of the Effect of Linoleic Acid on the Expression Level of MicroRNA-106b and MicroRNA-20a and their Related Target MHC Class I Chain-related Protein A in Docetaxel-treated Gastric Cancer Cells - Najibeh Shekari; Tohid Kazemi; Maedeh Moradi; Elham Eghbali; Bita Sepehri; Vahid Khaze Shahgoli; Masoud Shirmohamadi (Middle East Journal of Cancer, 2021)
Background: MicroRNAs are involved in response to therapeutic agents and have the ability to regulate the expression level of the targets associated with cancer growth and progression. As a dangerous signal in tumor cells, increased expression level of MHC class I chain-related protein A (MICA) could activate the immune system and induce responses to tumor cells. We conducted the present research to study the effect of linoleic acid (LA) and docetaxel alone or in combination with miR-106b, miR-20a, and MICA expression level in metastatic gastric cancer (GC) cell line MKN-45. Method: The study was an in vitro study using the gastric cancer cell line MKN- 45, which was cultured and treated with docetaxel and LA. Subsequently, the expression level of miR-106b, miR-20a, and MICA were assessed with quantitative real-time polymerase chain reaction. Results: MiR-106b decreased in LA and LA/docetaxel (P < 0.0001 and P = 0.002),and increased in docetaxel alone (P = 0.01). Meanwhile, miR-20a significantly decreased in docetaxel and LA/docetaxel (P < 0.0001), increased in LA treatment (P = 0.02). Regarding MICA, it significantly decreased in all the treated cells (P < 0.0001, P<0.0001, and P=0.0002 for docetaxel, LA and docetaxel/LA, respectively) but with different reduction intensities. Conclusion: Using LA or docetaxel alone had a different effect on miR-106b, miR-20a, and MICA expression level, yet in a simultaneous treatment, their positive effects were intensified. LA enhanced the effect of docetaxel concerning the expression level of miR-106b, miR-20a, and MICA and vice versa, which suggested that LA could be employed as an effective complementary agent in GC along with docetaxel.